Two Women Who Pioneered User-Centered Design - Grudin, Jonathan; Williams, Gayna (ACM Interactions, 2013)
Histories of HCI emphasize Vannevar Bush and the engineers and scientists who in the 1960s envisioned what computers would make possible: J.C.R. Licklider, Douglas Engelbart, Ted Nelson, Alan Kay, and Nicholas Negroponte. Their words and the prototypes of Engelbart and Ivan Sutherland have inspired countless researchers. In two conversations, Don Chaffin and Judy Olson suggested the field would benefit from a closer examination of the work of Lillian Gilbreth and Grace Hopper, whose relationships to HCI had been overlooked. They were right.